Aggregate Estimations in Bihar Soils by Different Methods - Singh, B.P.; Chtterjee, B.N. (Journal of Soil and Water Conservation, 2022)
The water-stable•aggregates of Bihar soils, under cultivated and uncultivated conditions, were determined by 4 different methods. The values of aggregations were high in Dry sieving method (71.91%), followed by Yoder's mechanical method of wet (wetting in Ethyl alcohol) sieving (69.87%), Yoders mechanical wet sieving method (34.39%) and Clement and Williams' hand wet sieving method 27.61%). Dry sieving did not give any indication of the stability of the aggregates in water as deter-mined by Yoder's method. The aggregate contents of soils determined by dry sieving -did not significantly differ from Yoder's method with 30 minutes wetting in Ethyl alcohol. Water-stable-aggregate contents determined by Yoder's mechanical wet sieving and Clement and Williams' hand wet sieving methods also did not differ significantly.